2008
DOI: 10.1007/s11090-008-9133-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Microwave Helium Plasma Torch Operating at Atmospheric Pressure to Destroy Trichloroethylene

Abstract: We examined the influence of the gas flow-rate, microwave power and trichloroethylene concentration on the destruction of trichloroethylene with a system based on a microwave helium plasma operating at atmospheric pressure. Based on the experimental results obtained, the proposed system allows input concentrations of C 2 HCl 3 in the ppmv range to be reduced to output concentrations in the ppbv range (i.e. virtually quantitative destruction) by using a microwave plasma power below 1000 W. High helium flow-rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…With an argon or helium plasma at atmospheric pressure, this system was proven to be effective at destroying carbon tetrachloride and trichloroethylene [21][22][23], and destruction rates greater than 99% were achieved. Using air as the main gas decreases the cost of the process because air can be obtained from the atmosphere, while argon and helium must be purchased.…”
Section: Introductionmentioning
confidence: 99%
“…With an argon or helium plasma at atmospheric pressure, this system was proven to be effective at destroying carbon tetrachloride and trichloroethylene [21][22][23], and destruction rates greater than 99% were achieved. Using air as the main gas decreases the cost of the process because air can be obtained from the atmosphere, while argon and helium must be purchased.…”
Section: Introductionmentioning
confidence: 99%
“…At a microwave power settings from 400 to 800 W, the SiCl 4 output concentration decreased and the contaminant destruction efficiency increased with increasing power. A concentration range exists where the destruction efficiency is maximal that changes with the microwave power [17]. The curves are similar in shape for any microwave power, and SiCl 4 concentration above 1.0% leads to an increased output concentrations of SiCl 4 caused by a decreased residence time in the plasma and result in a poorer destruction efficiency.…”
Section: Destruction Of Silicon Tetrachloridementioning
confidence: 86%
“…The electron density is deduced from Stark broadening measurements of the H β line [19,20], recorded using a [8][9][10][11][12][13][14][15]. The electron temperature could not be measured due to the experimental lack of precision.…”
Section: Optical Diagnosticsmentioning
confidence: 99%
“…These studies have shown that the TIA could be efficient in applications such as analytical chemistry [13] (in relation also with its ability to create chemically active species), surface treatment [14] and gas treatment [15].…”
Section: Introductionmentioning
confidence: 99%